Expression of CEA, CA125, CA19-9 and human milk fat globule membrane antigen in ovarian tumours. Issue 3 (March 1988) - Macdonald, F; Bird, R; Stokes, H; Russell, B; Crocker, J
Abstract : The expression of five different antigens in ovarian tumours was studied by means of an immunohistochemical test with anti-CEA, HMFG1 and HMFG2, NS19-9 and OC125 antibodies. Considerable variation was noted not only between different histological types and between tumours of one type but also between areas in a single tumour. HMFG1 and HMFG2 were the most reactive of all the antibodies; NS19-9 and OC125 were expressed by different populations of cells. It is concluded that specific combinations of antibodies are more effective both for the monitoring of ovarian cancer as well as for immunodiagnosis and treatment, than any single one used.